2000
DOI: 10.1103/physrevb.62.15047
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic polarons in manganites

Abstract: Using the Lanczos method in linear chains we study the double exchange model in the low concentration limit, including an antiferromagnetic super-exchange K. In the strong coupling limit we find that the ground state contains ferromagnetic polarons whose length is very sensitive to the value of K/t. We investigate the dispersion relation, the trapping by impurities, and the interaction between these polarons. As the overlap between polarons increases, by decreasing K/t, the effective interaction between them c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…1, the Mn 4 + cations are linked by O2 and O3 oxygens along the c direction, and the two Mn 4 + neighbors are also linked by Mn 3 + cations via O3 and O4 atoms. The magnetic indirect (Mn 4 + -O-Mn 3 + -O-Mn 4 + ) coupling mechanism should be super-exchange or double-exchange [32,33], because the lattice distortion in this compound leads to the degeneration within Mn1 3d (t 2g and e g ) and Mn2 3d (d 3z2 À r2 , d xy , d xz , and d yz ) orbitals. The double-exchange magnetic mechanism requires Mn 3 + (t 2g 3 , e g 1 ) and Mn 4 + (t 2g 3 , e g 0 ) as magnetically equivalent sites for e g electrons hopping and for maintaining the e g hole carrier concentration, however, the different spin arrangement and orbital occupation prevent the double-exchange magnetic interaction and in favor of the super-exchange magnetic interaction.…”
Section: Electronic Structurementioning
confidence: 99%
“…1, the Mn 4 + cations are linked by O2 and O3 oxygens along the c direction, and the two Mn 4 + neighbors are also linked by Mn 3 + cations via O3 and O4 atoms. The magnetic indirect (Mn 4 + -O-Mn 3 + -O-Mn 4 + ) coupling mechanism should be super-exchange or double-exchange [32,33], because the lattice distortion in this compound leads to the degeneration within Mn1 3d (t 2g and e g ) and Mn2 3d (d 3z2 À r2 , d xy , d xz , and d yz ) orbitals. The double-exchange magnetic mechanism requires Mn 3 + (t 2g 3 , e g 1 ) and Mn 4 + (t 2g 3 , e g 0 ) as magnetically equivalent sites for e g electrons hopping and for maintaining the e g hole carrier concentration, however, the different spin arrangement and orbital occupation prevent the double-exchange magnetic interaction and in favor of the super-exchange magnetic interaction.…”
Section: Electronic Structurementioning
confidence: 99%
“…[3][4][5]8,19 The three terms in the Hamiltonian describe, respectively, the kinetic energy of the itinerant electron, the Hund's-rule coupling between the electron and the localized spin on each site on the lattice, and the antiferromagnetic exchange between the localized spins. The symbols a i † and a i denote the creation and the annihilation operators for the electron state with spin at site i, ͗i j͘ denotes summation over nearest-neighbor sites, s i is the spin of the itinerant electron, and S i denotes the spin of the localized electron, the latter treated as classical spins.…”
Section: Hamiltonianmentioning
confidence: 99%
“…[9][10][11][12][13] Interest on the magnetic polaron problem has recently resurfaced in light of its relevance to a number of new systems, e.g., the high-T c materials and the colossal magnetoresistive manganites. [14][15][16][17][18][19] In this paper, we formulate a continuum model and solve it exactly using the Euler-Lagrange method and study the energetics and the spin structure of the magnetic polaron. The Euler-Lagrange equations are solved numerically using an iterative procedure that yields ''exact'' results in the sense that the solution can be obtained to any arbitrary accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors also found ferromagnetic polarons for the almost empty lower Kondo band (i.e. very few electrons) for S = 1/2 core spins [28,29], for the 1D AF Kondo model with few electrons [30], and for the 1D paramagnet at higher temperatures [31]. Small ferromagnetic droplets were predicted from energy considerations [32].…”
mentioning
confidence: 84%